Analisa Kelayakan Investasi Proyek Moda Transportasi Masal Light Rail Transit (LRT) Jabodebek - Rocky Francis Hunila; Suryo Utomo; Niluh Gede Annila Pradyani (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2023)
This journal aims to analyze the feasibility of investing in mass transportation development project in Indonesia, specifically LRT Jabodebek project using Capital Budgeting method. The author conducted an investment feasibility analysis using four Capital Budgeting methods, which consist of Payback Period (PP), Net Present Value (NPV), Profitability Index (PI), and Internal Rate of Return (IRR). In addition, there is also a sensitivity analysis to measure the impact of important variable changes on the analysis results. The analysis results show that the LRT Jabodebek project is a feasible project to continue, which indicated by PP duration of 22.59 years, NPV above 11 trillions rupiahs, PI of 1.42, and IRR of 8.09%. Sensitivity analysis shows that LRT Jabodebek project is still in the feasible category after being recalculated by applying several scenarios. This journal is expected to have significant implications for decision-makers and stakeholders in the public transportation investment sector in Indonesia.